Pŭrvo bienale na grafikata, Varna '81 - Aleksiev (1981)
Logo of organisation twice, in black, blue and white Poster advertising biennial graphics exhibition, Varna, May-September, 1981. Original title: Първо биенале на графиката, Варна '81 PO-0352